ANALYSIS PERFOMANCE ADDING V-GROOVE RIBLETS ON FLAP WITH NACA 43018 AIRFOIL - Ryan Wicaksono, Hilmi; Hariyadi, Setyo; Bagus Harianto, Bambang (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
Research on airfoils is a technological development in the world of aerodynamics. In this study, the analysis of aerodynamic characteristics of airfoils was carried out by simulating air on a test object in the form of NACA 43018 airfoil geometry which was given an extension in the form of riblets with variations in the shape of v-groove and plain wing. The existence of v-groove riblets, can delay the occurrence of separation. In this study, the analysis of aerodynamic characteristics of airfoils was carried out by simulating the air on the test object in the form of NACA 43018 airfoil geometry which was given an extension in the form of riblets with variations in the shape of v-groove and plain wing. The software used is ANSYS R22. Data processing using the Computational Fluid Dynamic (CFD) method. The simulation shows that the highest lift coefficient increase occurs at α = 12˚ with an increase of 2.9% lift coefficient and can reduce drag by 2.4% at α = 10˚ so it can be concluded by adding riblets to the airfoil can improve the performance of the Airfoil.